Tethered Cord and Anorectal Malformations: A Case Series - Destro, Francesca; Canazza, Lorena; Meroni, Milena; Selvaggio, Giorgio; Parazzini, Cecilia; Valentini, Laura; Riccipetitoni, Giovanna (European Journal of Pediatric Surgery, 2018)
Introduction The clinical manifestation of a stretched low-lying cone (LLC) is represented by the tethered cord syndrome (TCS) with cutaneous, urologic, neurologic, and orthopaedic dysfunctions. TC is frequently found in patients with anorectal malformations (ARMs). The aim of our article is to report a series of patients affected by LLC and ARMs and evaluate their management and long-term follow-up results.Materials and Methods We performed a retrospective analysis over a period of 15 years including patients with ARM and TC and excluding those with severe polymalformations. We collected information related to the types of malformations and demographic data. We analyzed their management (perinatal protocol, radiological investigations, surgery, and multidisciplinary follow-up). QOL was assessed through the International Classification of Functioning, Disability, and Health for Children and Youth (ICF-CY).Results Thirty-three patients among 210 ARM cases had TC (16%). Eleven of them underwent neurosurgery. One patient had retethering; out of 11 patients, 4 remained stable and 6 improved after surgery (UDS normalization and resolution of symptoms). At a mean follow-up of 10 years, four patients were on clean intermittent catheterization and five on the Peristeen transanal irrigation. The majority of patients were defined as 3 (from 1-bad to 5-excellent) for their physical and mental state.Conclusion The use of MRI is considered to complete the ARM screening in detecting TC. The multidisciplinary approach is crucial and helps in defining the management of patients. In fact, it is not clear how the features of ARM and TC affect each other. The selection of cases for surgery should take into account the critical elements.
Keywords: tethered cord; anorectal malformations; pediatric surgery; neurosurgery